Prototipo de vivienda sostenible en San Andrés Islas (2023)
The department of San Andrés Islas has been affected by climate change, in addition to the natural phenomena that have hit the island in recent years, such as Hurricane Iota in 2020, which left devastating damage to the island. Water supply, physical infrastructure, ecosystem goods and services, energy supplies, and the economy are also being affected.